Clinical value of the new International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification of lung adenocarcinoma. Issue 3 (21st February 2017) - Guo, Ziwei; Yi, Fumei; Yin, Wencheng; Zhang, Yu; Li, Qian; Gu, Yangchun; Xiao, Yu; Cao, Baoshan; Ma, Liwen; Liang, Li
Abstract : Background: We explored correlations between the new International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification, epidermal growth factor receptor ( EGFR ) mutation status, and prognosis. Methods: Data from 293 patients with lung adenocarcinoma were classified according to the new classification. Fisher's exact, χ 2, and log‐rank tests and Cox regression analysis were used to analyze correlations between EGFR mutation status, lung cancer prognosis, and the new histologic subtype. Disease‐free survival and progression‐free survival (PFS) were estimated using the Kaplan–Meier method. Results: Lepidic and non‐solid adenocarcinomas showed significantly elevated EGFR mutation rates (79.0% and 65.8%, respectively; P  < 0.05). EGFR mutation status was only associated with gender ( P  < 0.001). EGFR mutation‐positive patients who received targeted therapy had better median PFS than those who received chemotherapy as first‐line treatment ( P  < 0.001). The median PFS of patients with exon 19 and exon 21 mutations who received first‐line targeted therapy were 12.5 and 9.5 months, respectively ( P  = 0.970). Patients with micropapillary predominant adenocarcinomas had the shortest disease‐free survival (<18 months) and PFS. Histologic subtype ( P  = 0.036), treatment type ( P  = 0.031), and EGFR mutation status ( P  = 0.019) might be good prognostic factors for lung adenocarcinoma. Conclusion: Patients with exon 19 mutations obtained greater benefits from targeted therapy. In the new classification, EGFR mutation rates are higher in lepidic cases and in cases without the solid subtype. The micropapillary subtype of adenocarcinoma has the worst prognosis, while the lepidic subtype has the best.